(untitled) (Scientific journal of the Fergana State University, 2023)
In this following article places, person, things- objeccts, meaning subject names which is related to mourning ceremony in German and Uzbek languages will be analyzed and similarities and differences of them will be revealed with the help of examples in Uzbek and German languages.